Give to receive: private funding of science and corporate social responsibility - Catita, Sara Isabel Silva Borges (2009)
The thesis offers a general review about corporate social responsibility (CSR) and some related subjects like CSR strategies, relation with stakeholders, cause related marketing, social marketing, sponsorship and patronage. We then discuss funding for science and how the process to obtain it is structured, as well as a practical perspective of the funding process of a private science institution. From the general public perspective, this thesis provides a preliminary study of the opinion that Portuguese people have about Science, scientists and science related events. We focus primarily on the Researcher’s Night 08 event, on how the funding was obtained for it and the partnerships that were created in this context. We also explore ways to fund scientific research in Portugal in partnership with companies. We extend the research in detail to the Portuguese reality and analyze the results of the event from the perspective of the general public and partner companies involved. We also detail the CSR strategy of a Portuguese telecommunication company that participated in the event. Finally, this research suggests about how to promote Science in companies as a good CSR strategy. We also study the role of information and openness inside these partnerships as a key for a successful strategy.